Favorable outcome with sentinel lymph node biopsy alone after neoadjuvant chemotherapy in clinically node positive breast cancer at diagnosis: Turkish Multicentric NEOSENTI-TURK MF-18-02-study. Issue 10 (October 2021) - Cabıoğlu, N.; Karanlık, H.; Yıldırım, N.; Müslümanoğlu, M.; Çakmak Karadeniz, G.; Trabulus Can, D.; Tükenmez, M.; Ersoy, Y.E.; Uras, C.; Zengel, B.; Emiroğlu, S.; Polat, A.K.; et al.
Abstract: Purpose: Factors affecting local outcome were evaluated in patients with clinically node-positive (cN+) breast cancer at diagnosis, who underwent sentinel lymph node biopsy (SLNB) alone after neoadjuvant chemotherapy (NAC). Methods: Between 2004 and 2018, 303 cytopathology-proven cN (+) patients in a multicentric registry, who received NAC and underwent SLNB alone were analysed. All patients had regional nodal irradiation. Results: Median age was 46 (23–70). Of those, 211 patients had ypN0 disease (69.6%), whereas 92 patients had ypN (+) disease including 19 (20.6%) isolated tumor cells (ITC), 33 micrometastases (35.9%) and 40 macrometastases (43.5%). At a median follow-up of 36 months (24–172), one patient (0.3%) with macrometastatic SLN was found to have locoregional recurrence as chest wall and supraclavicular LN metastases at the 60th month. Five-year disease-free survival (DFS) and disease specific survival (DSS) rates were 87% and 95%, respectively. Patients with cT3/4 (HR = 2.41, 95% CI; 1.14–5.07), non-luminal molecular pathology (HR = 2.60, 95% CI, 1.16–5.82), and non-pCR in the breast (HR = 2.11, 95% CI, 0.89–5.01) were found to have an increased HR compared to others in 5-year DFS. However, no difference could be found between ypN0 and ypN ITC and micrometastasis (HR = 1.23, 95% CI, 0.44–3.47), whereas there was a slight increase in HR of patients with ypN macrometastasis versus ypN0 (HR = 1.91, 95% CI, 0.63–5.79). Conclusion: ALND could be avoided in meticulously selected cN (+) patients who underwent SLNB after NAC having breast and/or nodal pCR, cT1-2, or low volume residual nodal disease with luminal pathology, as long as axillary radiotherapy is provided.